Structural changes of silver polymer electrolytes: Comparison between poly(2-ethyl-2-oxazoline) and poly(N-vinyl pyrrolidone) complexes with silver salt - Kim, JH; Min, YR; Kim, CK; Won, J; Kang, YS (WILEY-BLACKWELL, 2004)
The difference between the polymer matrices of poly(2-ethyl-2-oxazoline) (POZ) and poly(N-vinyl pyrrolidone) (PVP) does not have a significant effect on the facilitated propylene transport and propylene solubility in 1:1 polymer/silver salt complex membranes, according to our previous work. In this article, its origin is investigated in terms of both microstructures of silver polymer electrolytes and the coordinative interaction of silver ion with polymer and with the counteranion. Initially different microstructures of POZ and PVP become similar to each other upon dissolving a large amount of silver salt, as evidenced by propane transport properties, specific volume, and Bragg d-spacing. The dissolution of the silver salt in the polymer solvent strongly depends on the coordinative interaction between silver ion and carbonyl oxygen of POZ and PVP. Thus, the structural similarity upon dissolving silver salts in POZ and PVP is primarily determined by the coordinative interaction between silver ion and carbonyl oxygen, which was confirmed by theoretical structure calculation based on density functional theory and by IR and Raman spectroscopy. Therefore, facilitated olefin transport for silver polymer electrolyte membranes does not strongly depend on the polymeric matrix at high silver concentrations. (C) 2003 Wiley Periodicals, Inc.
Keywords: FACILITATED OLEFIN TRANSPORT; EFFECTIVE CORE POTENTIALS; MOLECULAR CALCULATIONS; POLY(ETHYLENE OXIDE); ION ASSOCIATION; SOLAR-CELLS; SOLID-STATE; PROPYLENE; MEMBRANES; NACF3SO3